Metallothionein – Immunohistochemical Cancer Biomarker: A Meta-Analysis - Gumulec, Jaromír; Raudenská, Martina; Adam, Vojtěch; Kizek, René; Masařík, Michal (PLOS, 2014)
Metallothionein (MT) has been extensively investigated as a molecular marker of various types of cancer. In spite of the fact that numerous reviews have been published in this field, no meta-analytical approach has been performed. Therefore, results of to-date immunohistochemistry-based studies were summarized using meta-analysis in this review. Web of science, PubMed, Embase and CENTRAL databases were searched (up to April 30, 2013) and the eligibility of individual studies and heterogeneity among the studies was assessed. Random and fixed effects model meta-analysis was employed depending on the heterogeneity, and publication bias was evaluated using funnel plots and Eggers tests. A total of 77 studies were included with 8,015 tissue samples (4,631 cases and 3,384 controls). A significantly positive association between MT staining and tumors (vs. healthy tissues) was observed in head and neck (odds ratio, OR 9.95; 95% CI 5.82– 17.03) and ovarian tumors (OR 7.83; 1.09–56.29), and a negative association was ascertained in liver tumors (OR 0.10; 0.03–0.30). No significant associations were identified in breast, colorectal, prostate, thyroid, stomach, bladder, kidney, gallbladder, and uterine cancers and in melanoma. . However, a high degree of inconsistence was observed in several tumor types, including colorectal, kidney and prostate cancer. Despite the ambiguity in some tumor types, conclusive results are provided in the tumors of head and neck, ovary and liver and in relation to the tumor grade and patient survival.

Metallothionein (MT) has been extensively investigated as a molecular marker of various types of cancer. In spite of the fact that numerous reviews have been published in this field, no meta-analytical approach has been performed. Therefore, results of to-date immunohistochemistry-based studies were summarized using meta-analysis in this review. Web of science, PubMed, Embase and CENTRAL databases were searched (up to April 30, 2013) and the eligibility of individual studies and heterogeneity among the studies was assessed. Random and fixed effects model meta-analysis was employed depending on the heterogeneity, and publication bias was evaluated using funnel plots and Eggers tests. A total of 77 studies were included with 8,015 tissue samples (4,631 cases and 3,384 controls). A significantly positive association between MT staining and tumors (vs. healthy tissues) was observed in head and neck (odds ratio, OR 9.95; 95% CI 5.82– 17.03) and ovarian tumors (OR 7.83; 1.09–56.29), and a negative association was ascertained in liver tumors (OR 0.10; 0.03–0.30). No significant associations were identified in breast, colorectal, prostate, thyroid, stomach, bladder, kidney, gallbladder, and uterine cancers and in melanoma. . However, a high degree of inconsistence was observed in several tumor types, including colorectal, kidney and prostate cancer. Despite the ambiguity in some tumor types, conclusive results are provided in the tumors of head and neck, ovary and liver and in relation to the tumor grade and patient survival.
Metallothionein – Immunohistochemical Cancer Biomarker: A Meta-Analysis
Keywords: heterogeneity; imunohistochemistry; Metalothionein; heterogeneity; imunohistochemistry; Metalothionein